2003
DOI: 10.1073/pnas.1133324100
|View full text |Cite
|
Sign up to set email alerts
|

Survey of naturally occurring CD4 + T cell responses against NY-ESO-1 in cancer patients: Correlation with antibody responses

Abstract: NY-ESO-1 is one of the most immunogenic proteins described in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
185
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(192 citation statements)
references
References 23 publications
(27 reference statements)
6
185
1
Order By: Relevance
“…It was also shown that patients with high antibody titers against NY-ESO-1 produce an effective CD8 + T cell response (22). Moreover, a clear correlation of an NY-ESO-1-specific antibody response and NY-ESO-1-specific CD4 + T cells was described (34). In summary, an orchestrated interaction of different parts of the immune system seems to be necessary to generate an efficient and durable immune response.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that patients with high antibody titers against NY-ESO-1 produce an effective CD8 + T cell response (22). Moreover, a clear correlation of an NY-ESO-1-specific antibody response and NY-ESO-1-specific CD4 + T cells was described (34). In summary, an orchestrated interaction of different parts of the immune system seems to be necessary to generate an efficient and durable immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In NY-ESO-1-expressing gastric tumors, the overall frequency of antibody positivity was 11%, but it increased with disease progression (34). Importantly, humoral immune response to NY-ESO-1 has been shown to predict both CD8 and CD4 T-cell responses to NY-ESO-1 (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The highly restricted expression pattern of NY-ESO-1 in normal tissues (testis), its frequent expression in a wide variety of cancers, and the spontaneous humoral and cellular immune responses elicited by NY-ESO-1 in a subset of patients with NY-ESO-1-expressing tumors are highly favorable characteristics for a vaccine target (1,5,6,16). Immunological assays to detect antibody and CD4 and CD8 T cell responses to NY-ESO-1 are well advanced and provide a secure basis for monitoring spontaneous and vaccine-induced immune responses and for comparing the immunogenicity of different NY-ESO-1 vaccine constructs (4,16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous immune responses involving antibody as well as CD4 and CD8 T cells directed against a broad range of MHC class I-and class II-restricted NY-ESO-1 peptides have been observed in patients with advanced NY-ESO-1-expressing tumors (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%